Advance Care Planning for People with Dementia in Western Australia: An Examination of the Fit Between the Law and Practice*. Issue 2 (4th March 2018) - Blake, Meredith; Doray, Olivia Nicole; Sinclair, Craig
Abstract: This article examines the 'fit' between the Western Australian legislation on advance care planning (ACP) and health professionals' experiences implementing this in relation to persons with dementia. The legislative provisions are outlined, and a qualitative study of experiences with ACP among 19 health professionals, all engaged in the care of persons with dementia, is described. Based on these interviews, the authors propose three themes: 'navigating risk', 'the therapeutic journey' and 'the most agreeable outcome' to describe current practice in this area. The authors conclude that ACP in this context is aimed at minimising risk, establishing consensus and achieving the 'most agreeable outcome' for the person and their family, rather than privileging the individual autonomy of the person engaging in ACP. The implications for policy and law makers regarding possible reform of ACP in relation to persons with dementia are discussed.